Inside the Nation of Islam : a historical and personal testimony by a Black Muslim - White, Vibert L., Jr (University Press of Florida, 2001)
This detailed study of the internal workings of the Nation of Islam under the leadership of Louis Farrakhan examines the evolution of the organization since 1977 and its strange ideological menu of Black Nationalism, political-economic development, anti-Semitism, and conservative Republican ideals. Vibert White maintains that Farrakhan's Nation has become a cult that utilizes black nationalistic and religious dogma and its ability to create political and racial controversy to exploit poor and working-class black Americans for the leaders' economic and political gain. At the heart of Inside the Nation is White's chronicle of his own sojourn during the 1980s and 1990s as a registered Muslim--from his days as a foot soldier in the Fruit of Islam, the Nation's military organization, through his rise to the status of minister and advisor to the leadership. Included are White's dealings with such leaders as Louis Farrakhan, Akbar Muhammad, Khallid Muhammad, and Benjamin Chavis Muhammad and his involvement in such activities as the Million Man March. As one who traveled for the organization throughout Europe, Africa, the Middle East, and the United States, White was able to observe the leadership and the operation of the group at close hand. He reveals for the first time the detailed structure of NOI's business and religious operation. He explores and separates the Nation of Islam, the religious arm that is incorporated only in Chicago, from the Final Call, its business center operated only by the Farrakhan family. As a professional historian, White was able to separate the passion of the group's rhetoric from its real objectives, which centered on building a personal empire for Louis Farrakhan.